HUBUNGAN PENGETAHUAN, SIKAP, DUKUNGAN TENAGA KESEHATAN DAN DUKUNGAN KELUARGA TERHADAP PELAKSANAAN PROTOKOL KESEHATAN 3M DI MASA COVID 19 - Evi Hasnita, Indreswati, Berliana Mega Indreswati, Berliana Mega (Universitas Fort de Kock Bukittinggi, 2021)
Data update on March 1, 2021, the number of positive COVID-19 cases was 29,204 people, with information as many as 229 people being treated, 791 people doing self-isolation, 37 people in regional isolation, 647 people died, and 27,500 people were declared cured. This study aims to determine the relationship between Knowledge, Attitude, Support of Health Workers and Family Support on the Implementation of the 3M Health Protocol during the Covid 19 Period in the Productive Age Community (20-45 Years) in Tarok Dipo Village, Bukittinggi City in 2021. This research is analytic with cross sectional approach. Test statistics using Chi-square. The research instrument was using a questionnaire. This study used univariate and bivariate analysis. The population in this study is people with an age range of 20-45 years as many as 4,003 people and the number of samples used is 98 people with random sampling techniques. The results of the study showed that of the 98 respondents who had low knowledge of the implementation of the 3M health protocol by 51.0%, 68.4% poor attitude, 50.0% less supportive health workers, 82.7% families who did not support the implementation of the 3M health protocol. based on the results of the chi-aquare test, the p-values between knowledge, attitudes, support from health workers, and family support regarding the implementation of the 3M health protocol were 0.021, 0.026, 0.386, and 0.024. Based on the results of this study, knowledge, attitudes, and family support have a relationship with the implementation of the 3M health protocol while the support of health workers has no relationship with the implementation of the 3M protoco